2006
DOI: 10.1523/jneurosci.4178-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Compartment-Dependent Colocalization of Kir3.2-Containing K+Channels and GABABReceptors in Hippocampal Pyramidal Cells

Abstract: G-protein-coupled inwardly rectifying Kϩ channels (Kir3 channels) coupled to metabotropic GABA B receptors are essential for the control of neuronal excitation. To determine the distribution of Kir3 channels and their spatial relationship to GABA B receptors on hippocampal pyramidal cells, we used a high-resolution immunocytochemical approach. Immunoreactivity for the Kir3.2 subunit was most abundant postsynaptically and localized to the extrasynaptic plasma membrane of dendritic shafts and spines of principal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
145
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(165 citation statements)
references
References 75 publications
(91 reference statements)
13
145
1
5
Order By: Relevance
“…Its sensitivity to both CGP55845 and tertiapin-Q suggests instead that GABA released along the axon of the recorded GC activates GABAB autoreceptors coupled to GIRK channels. Although coupling of presynaptic GABAB receptors to transmitter release may involve modulation of Ca 2ϩ rather than K ϩ channels (Lüscher et al, 1997), several recent reports reveal the presence of presynaptic GIRK channels (Kulik et al, 2006;Ladera et al, 2008;Michaeli and Yaka, 2010) that may be coupled to GABAB receptors (Kulik et al, 2006;Lujan et al, 2009). The mechanisms by which activation of GIRK channels may induce prolonged (Ͼ30 s) changes in axonal excitability remain to be fully characterized but may involve hyperpolarization-induced, deinactivation of potassium currents.…”
Section: Discussionmentioning
confidence: 99%
“…Its sensitivity to both CGP55845 and tertiapin-Q suggests instead that GABA released along the axon of the recorded GC activates GABAB autoreceptors coupled to GIRK channels. Although coupling of presynaptic GABAB receptors to transmitter release may involve modulation of Ca 2ϩ rather than K ϩ channels (Lüscher et al, 1997), several recent reports reveal the presence of presynaptic GIRK channels (Kulik et al, 2006;Ladera et al, 2008;Michaeli and Yaka, 2010) that may be coupled to GABAB receptors (Kulik et al, 2006;Lujan et al, 2009). The mechanisms by which activation of GIRK channels may induce prolonged (Ͼ30 s) changes in axonal excitability remain to be fully characterized but may involve hyperpolarization-induced, deinactivation of potassium currents.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we found that GABA B receptors undergo endocytosis in dendritic spines and shafts within minutes of NMDA receptor activation. Notably, endocytosis prevents GABA B receptors from activating effector K + channels that cluster with GABA B receptors in spines (12).…”
Section: Discussionmentioning
confidence: 99%
“…Well-known effectors of dendritic GABA B receptors are the Kir3-type K + channels, which cluster with GABA B receptors in spines (12). We used whole-cell patch-clamp recording to address whether NMDA-treatment reduces baclofen-induced K + currents due to GABA B receptor internalization.…”
Section: Nmda Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…By performing SDS-digested freeze-fracture replica immunolabeling (Hagiwara et al, 2005;Kulik et al, 2006), we found ␤1-integrin in presynaptic compartments of CA1 synapses. Anti-SNAP25 labeling was used to identify presynaptic compartments (Fig.…”
Section: Presynaptic Localization Of ␤1-integrin In Ca1 Synapsesmentioning
confidence: 94%